Design, synthesis and biological screening of novel 1,3,4-oxadiazoles as antitubercular agents - Tambe, Macchindra S.; Choudhari, Amit; Sarkar, Dhiman; Sangshetti, Jaiprakash; Patil, Rajesh; Gholap, Somnath S. (Chemistryselect, 2018)
A series of novel 2,5-disubstitued 1,3,4-oxadiazole derivatives bearing 2,2-dimethyl-2,3-dihydrobenzofuran scaffold has been synthesized and screened for antitubercular activity. All the synthesized compounds were characterized by IR, H-1 NMR, C-13-NMR and Mass spectral study. The in vitro antitubercular activity of the synthesized compounds was evaluated against Mycobacterium tuberculosis H37Ra(ATCC 25177) strain. Among the synthesized compounds, four compound displayed good antitubercular activity IC50 values in low micro-gram range (<10 mu g/mL). The antitubercular data suggested that growth inhibition MTB can be imparted by the introduction of a 4- trifluoromethyl phenyl acetylene substituent. Specificity of these compounds was checked by screening them for their anti-bacterial activity against four bacterial strains (Gram-negative strains: E. coli, S. aureus; Gram-positive strains: P. aeruginosa and B. subtilis). None of the compound displayed antibacterial activity against any of the seleted strain. Molecular docking studies were carried out on InhA (FabI/ENR) which shows that the synthesized compounds bind at the catalytic site in a most favourable manner suggesting their potential as anti-mycobacterial agents. The research presented here was found to be adventitious for the development of new therapeutic agents against Mycobacterium infection.